Pernikahan Dini Sebagai Bukti Nyata Indonesia Darurat SEX Education Pada Eks Pelajar Di Sulawesi Selatan - Mario Mario (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
The phenomenon of early marriage often occurs in Indonesia. This has been happening for a long time in several areas spread across parts of Indonesia, especially in interior and rural areas. This is due to the social and cultural aspects of the local community. The distinctive characteristics of the social culture of the community are behavior, arts, customs, morals, laws, knowledge and beliefs of the community. Early marriage is experienced by many teenagers under the age of 18. This problem has actually been discussed in the 1954 Declaration of Human Rights which opposes early child marriage, but in fact the practice of early marriage is still being carried out, not only in a few regions but also in other parts of the world where this practice is still considered a tradition. in their society which needs to continue to be passed down to the next generation. The applicable laws seem to be ineffective because they are defeated by the customs that govern a group.